Microwave-Assisted Preparation of Zinc-Doped β-Tricalcium Phosphate for Orthopedic Applications - Ali Taha Saleh; Dheyaa Alameri (Indonesian Journal of Chemistry, 2021)
A novel two-step methodology delivering zinc into the structure of β-tricalcium phosphate (β-TCP) has been investigated. Incorporating wet precipitation of calcium-deficient apatite [Ca9-xZnx(HPO4)(PO4)5(OH)] (x = 0.00–1.00 mol) using a microwave-assisted process followed by two-hour calcination at 1000 °C has been conducted to generate a ratio of 1.48 of Zn doped β-TCP. The products were characterized by X-ray diffraction (XRD), Fourier-transform infrared (FTIR) spectrometer, and field emission scanning electron microscope (FESEM). Our results confirmed that the product was crystalline Zn2+-doped β-tricalcium phosphate. The incorporation of Zn+2 into the β-TCP lattice resulted in a shifting of diffraction peaks to higher 2θ values, which were attributed to the substitution of larger-sized Ca+2 ions with smaller-sized Zn2+ ions. A reduction in the intensity of the XRD peaks was also observed due to the reduction in the degree of crystallinity of the samples. Lattice parameters along the a and c-axis showed a gradual decrease in length with an increase in the amount of Zn2+ doping. This decrease was attributed to the replacement of Ca+2 ion by the smaller-sized Zn2+ ions. The microstructure of the powders consisted of microscale aggregates fused together. EDX analysis of all samples showed that the Zn2+ doping had successfully taken place and the amount of Zn2+ present in the samples was in good agreement with the theoretical values.